The influence of opposition quality on team performance indicators in elite Gaelic football. (3rd September 2021) - McDermott, Liam; Collins, Kieran; Mangan, Shane; Warne, Joe
ABSTRACT: The aim of the current study was to assess if opposition quality influences the technical performance of lower-ranked Gaelic football teams. Over a three-year period (2016–2018), nine teams from Tier 3 were assessed on their technical performance levels over 50 matches. Teams were split into three groups according to team rating determined objectively using the Elo Ratings System for Gaelic football (Tier 1 (n = 14) (>1500 points, highest ranking), Tier 2 (n = 17) (1200–1499 points) and Tier 3 (n = 19) (<1200 points)). Teams in Tier 3 are of the same ranking as the "lower ranked teams". A series of 1-Way ANOVA's examined differences in technical performance comparing the lower ranked teams to all 3 tiers, where both significance and effect size were considered. There was a non-significant difference found when comparing the lower ranked teams with all three tiers for all variables (all P > 0.05). For both successful hand-passes (ƞ 2 = 0.140) and long kick-outs lost (ƞ 2 = 0.213), all tiers had a large effect. Between tiers, long kick-outs lost (d = 1.77) was the only large effect noted and occurred when the lower ranked teams played Tier 1 teams. The current study gives an insight to coaches of what parameters in the game are influenced by the opposition.